SIDE EFFECTS MONITORING OF AMINOGLYCOSIDE ANTIBIOTIC IN HOSPITALIZED PATIENTS - Sari, Santi Purna; Sartika, Siti Syarah; Rianti, Alfina (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to monitor the side effects in patients who received aminoglycoside antibiotics at the inpatient service of Fatmawati Hospital from March to May 2017. Methods: This was an observational study based on data collected through patient interview, prescribing information, and medical records. Data were collected on all inpatients treated with aminoglycosides during the study period (total sampling method). The Naranjo algorithm was used to assess the causality of the observed effects. Results: The data from 33 patients were evaluated, among whom 14 (42.4%) developed nephrotoxicity and 5 (15.2%) had ototoxicity. Based on the Naranjo algorithm analysis, the five cases of ototoxicity were categorized as probable drug side effects. No correlation was found between any of the side effects and either age (p=0.726) or sex (p=0.620). Conclusion: In this evaluation of the side effects attributable to aminoglycoside antibiotics in hospitalized patients, nephrotoxicity was the most common, followed by ototoxicity. The latter was deemed probable drug-related side effects based on the Naranjo algorithm. Of the other side effects, twice as many were considered probable as those thought to be possible drug side effects. Neither age nor sex was significantly related to the adverse effects secondary to gentamicin or amikacin.